(untitled) (Journal of Agriculture & Rural Development, 2010)
In a laboratory experiment seeds of four maize varieties viz., BARI hybrid maize -5, BARI hybrid maize -2, BARI maize -7 and BARI maize -5 were germinated at 24, 30 and 36°C to study seed metabolic activity and seed reserve translocation. Temperature had significant effect on germination characteristics and seed reserves mobilization. The shoot dry weights were increased with the increase of temperature from 24 to 36°C. But in root dry weight and length of shoot and root the highest value was found at 30°C compared to 24 to 36°C. At moderate temperature (30°C) all the varieties showed highest seed metabolic efficiency (SME) than those of at 24 and 36°C temperature and hybrid varieties BARI hybrid maize -2 and BARI hybrid maize -5 attained higher seed metabolic efficiency than the BARI maize -5 and BARI maize -7. Key words: Maize; temperature; germination; seed metabolic efficiency. DOI: 10.3329/jard.v7i1.4421 J Agric Rural Dev 7(1&2), 51-56, June 2009